THE CONCEPT OF “ELDERLY CITIZENS” IN THE INDONESIAN CONSTITUTION: A CRITICAL ANALYSIS - Hertanto, Ari Wahyudi; Arinanto, Satya; Rizal, Jufrina (UI Scholars Hub, 2022)
Human existence is the most important element of the law and the state. They contribute greatly to the growth and development of a nation. Despite their great contribution, all human beings will experience a gradual decrease in their physical and psychological capacity due to ageing. According to the latest Central Statistics Agency report, there exists 29.3 million elderly citizens in Indonesia. This figure is equivalent to 10.82% of the total population. To anticipate this demographic condition, the government ought to ensure the welfare of its elderly citizens in accordance with the mandate of the 1945 Constitution. However, the 1945 Constitution does not specifically regulate the term “elderly citizen”. Human beings who are considered as legal subjects under the 1945 Constitution are simply referred to as “citizen.” The term “elderly citizen” can only be found under Law Number 13 of 1998 concerning the Welfare of Elderly Citizens. Although the law is intended to provide sufficient social and legal protection to elderly citizens, it has not yet to grasp the essence of elderly citizen as an overall legal subject. This is indicated by the use of the term “Potential Elderly Citizen” and “Non-Potential Elderly Citizen” in its provisions. Therefore, a more in-depth legal study regarding human beings (elderly citizens) as an overall legal subjects is required. This article tries to answer how elderly citizens are viewed theoretically as legal subjects, how the 1945 Constitution regulates elderly citizens as overall legal subjects, and how the concept of elderly citizens is critically interpreted as a form of reorientation.